Sosialisasi Eco-Drainage (Drainase berwawasan lingkungan) dalam meminimalisir genangan dan banjir di Desa Napai - ULVI, ULVIZA; Rifan, Muliadi; Cut Suciatina, Silvia (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2024)
Indonesia is one of the areas categorized as having a high level of risk of natural disasters, including floods. Flooding is a common problem in Napai Village, West Woyla Sub-district, West Aceh District. Napai Village has a high level of flood vulnerability, which when there is rain in high intensity causes this village to experience flood disasters. In 2021, floods hit Napai Village with a height of up to 50 cm which caused residents' houses to be submerged by floods and disrupted road access. In the PPK Ormawa program activities carried out by the HMTS-UTU PPK Omawa team which were carried out in Napai Village by holding socialization activities on the concept of eco-drainage in handling problems at partner locations. In the implementation of the activity the team gave questionnaires to the community as an indicator of the level of understanding of the community regarding the material presented. The results obtained after analyzing the questionnaire data were an increase in community understanding which reached 70%.